2022
DOI: 10.1177/03611981211067797
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Vehicle–Tire–Pavement Approach for Determining Pavement Structure–Induced Rolling Resistance under Dynamic Loading

Abstract: Pavement-related rolling resistances, caused by pavement–vehicle interaction, are important components of pavement life-cycle assessment (LCA). Structure-induced rolling resistance (SRR) is caused by dissipated vehicle kinetic energy in the pavement structure. This paper presents an integrated vehicle–tire–pavement approach to evaluate asphalt pavement SRR under dynamic loading. A three-dimensional (3D) semitrailer-truck model was used to calculate dynamic wheel loads on various pavement surface-roughness prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…They argued that a thicker AC layer would imply a larger volume of integration for energy dissipation, which results in a higher SRR ( 88 ). The latest studies use the concept of maximum pavement deflection (at certain baseline conditions) for SRR analysis, which is implicitly related to AC thickness, but also to all pavement structure stiffnesses ( 84 , 91 ).…”
Section: Theoretical Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…They argued that a thicker AC layer would imply a larger volume of integration for energy dissipation, which results in a higher SRR ( 88 ). The latest studies use the concept of maximum pavement deflection (at certain baseline conditions) for SRR analysis, which is implicitly related to AC thickness, but also to all pavement structure stiffnesses ( 84 , 91 ).…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…The effect of load proximity from the different heavy vehicle tires has been investigated numerically in the literature and it was found that SRR can be accurately calculated by simulating one tire and multiplying the output by the number of tires on the vehicle ( 58 , 87 ). Recently, the effect of dynamic load on SRR was investigated numerically by Liu and Al-Qadi ( 91 ) and it was shown that ignoring dynamic loading effect could result in 12% error in SRR prediction. The latter result seems to indicate that road roughness can interact with SRR.…”
Section: Theoretical Modelingmentioning
confidence: 99%
See 3 more Smart Citations